Penanganan Sampah Plastik Di Desa Medan Krio Menjadi Barang Berguna Siap Pakai Kab.Deli Serdang - Br.Sembiring; Mhd Rifki; Luthfita Khalisah Nst; Adly Hakim Nasution; Agung Gumelar (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One non-organic waste that is used extensively in daily life is plastic, particularly for food packaging vendors and as a raw material for toy manufacturers. Waste will result from the vast amount of plastic that residents of Medan Krio use and discard after consumption. The goal of the research program's implementation is to enable locals to recycle waste materials to create valuable products. The village of Medan Krio Village has a high population density, which has led to the development of waste management issues. The village has traditionally disposed of waste by burning it and throwing it beside the street, which is why there is a garbage stench. which has a strong odor as a result of careless trash dumping. In light of this issue, Ecobricks may offer a way to lessen plastic waste and turn it into products with a positive economic impact. Method: PAR (Participatory Action Research), which is study that identifies issues and then offers potential solutions. Findings: The Ecobrick technique is being used in Medan Krio Village to make use of plastic waste. A recycling technique known as